Productivity of japanese quails in relation to body weight at the end of the rearing phase - Vieira, Javer Alves [UNESP]; Garcia, Edivaldo Antônio [UNESP]; Molino, Andréa De Britto; Santos, Tiago Antônio Dos [UNESP]; Paz, Ibiara Correia De Lima Almeida [UNESP]; Baldo, Grace Alessandra De Araújo [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2016)
Two experiments were conducted at different times with the objective of investigating how the body weight of Japanese quails at the end of the rearing period may alter the performance during the laying phase. In both experiments, the birds were distributed in five treatments according to their body weights, which were obtained at 42 and 35 days of age for the first and second experiments respectively, and the following categories were considered for said experiments: very light, light, average, heavy and very heavy. For both experiments, the treatments were distributed in a randomized block design, at eight repetitions per treatment for the first one and six for the second one, both at 18 birds per repetition. During the first experiment, sexual maturity, laying percentage, marketable egg percentage, average egg weight and egg mass, in second experiment, feed consumption, final body weight, eggs per bird present, laying percentage, average egg weight, egg mass and alimentary conversion were evaluated. The results obtained show that Japanese quails whose body weight is lower than 140 grams at 42 days of age, or lower than 120 grams at 35 days of age show significantly worse productive results during the laying phase.

Dois experimentos foram conduzidos para investigar como o peso corporal de codornas japonesa ao final do período de recria pode alterar os parâmetros de desempenho durante a fase de postura. Nos dois experimentos as aves foram distribuídas em cinco tratamentos em função do peso corporal, estes foram obtidos aos 42 e aos 35 dias de idade, para o primeiro e segundo experimento respectivamente. Para ambos os experimentos foram consideradas as classes: muito leves, leves, peso médio, pesadas e muito pesadas. Os tratamentos foram distribuídos em delineamento em blocos ao acaso, com oito repetições por tratamento para o primeiro experimento e seis repetições por tratamento para o segundo experimento, ambos com 18 aves por repetição. No primeiro experimento, foram avaliados a maturidade sexual, a porcentagem de postura, a porcentagem de ovos comercializados, o peso médio dos ovos e massa de ovos. No segundo experimento foram avaliados o consumo de ração, o peso corporal final, os ovos por ave presente, a porcentagem de postura, o peso médio dos ovos, massa de ovos e a conversão alimentar. Os resultados mostram que codornas com peso corporal inferior a 140 gramas aos 42 dias de vida, ou inferior a 120 gramas aos 35 dias de vida, pioram significativamente os resultados produtivos durante o período de postura.
Produtividade de codornas japonesas em função do peso corporal ao final da fase de recria
Keywords: body development; egg production; quail production; sexual maturity; peso corporal; produção de ovos; coturnicultura; maturidade sexual